The First Algorithm Calculating Cement Injection Volumes in Patients with Spine Metastases Treated with Percutaneous Vertebroplasty - Cui Y; Pan Y; Lei M; Mi C; Wang B; Shi X (Dove Medical Press, 2020)
Yunpeng Cui,1,* Yuanxing Pan,1,* Mingxing Lei,2 Chuan Mi,1 Bing Wang,1 Xuedong Shi1 1Department of Orthopedic Surgery, Peking University First Hospital, Beijing, People’s Republic of China; 2Department of Orthopedic Surgery, Hainan Hospital of Chinese PLA General Hospital, Sanya, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuedong ShiDepartment of Orthopedic Surgery, The Peking University First Hospital No. 8 Xishiku Street, Xicheng District Beijing 100032 People’s Republic of ChinaTel +86-010-83572211Email 172998774@qq.comPurpose: This study aims to develop an algorithm to predict cement injection volumes in patients with spine metastases treated with percutaneous vertebroplasty (PVP). Risk factors were also analyzed for intra-spinal canal cement leakages.Patients and Methods: A retrospective analysis of 584 vertebrae in 251 patients. Patients and vertebrae were divided into three groups based on grades of tumor invasion to the spinal cord. Patients with the complete posterior wall of vertebrae were classified into group A, patients without the complete posterior wall of vertebrae but with normal Dural sac were classified into group B, and patients with deformation of the Dural sac but without neurological symptom were classified into group C. We systematically reviewed demographic data, clinical parameters, radiology features, and cement leakages among the three groups. The multiple linear regressions were used to screen potential risk factors and develop the algorithm to predict injected cement volumes in vertebrae. Significant factors were included in the algorithm. Potential risk factors for intra-spinal canal cement leakage were analyzed using the multiple logistic regressions.Results: In the study, 17.1% (100/584) of vertebrae occurred cement leakages. Vertebrae in group C (28.6%, 8/28) had the highest cement leakage rate than patients in group A (14.4%, 61/424) and B (23.5%, 31/132) (P=0.014). Vertebrae in group C (14.3%, 4/28) were also more prone to intra-spinal canal leakages (P=0.003). The multiple logistic analysis showed that the Bilsky scale was significantly associated with intra-spinal canal cement leakages (P< 0.001). The multiple linear regression analysis showed that intercept (P< 0.001), treated vertebrae level (P< 0.001), cortical osteolytic destruction in posterior wall (P< 0.001), and Bilsky scale (P=0.014) were significant and those variables were included in the algorithm. The algorithm was Y=3.1627－0.8677×treated vertebrae level－0.6182×cortical osteolytic destruction in the posterior wall－0.2819×Bilsky scale.Conclusion: An algorithm is proposed and can be used to calculate cement injection volumes in spine metastases treated with PVP. This algorithm can facilitate surgical planning and guide cement injections. Bilsky scale is an independent risk factor for intra-spinal canal cement leakages. We do not recommend PVP treated in patients with a Bilsky scale of 2 and 3 mainly due to a high rate of intra-spinal canal cement leakages.Keywords: spinal metastases, percutaneous vertebroplasty, algorithm, intra-spinal canal leakages, risk factors